Giant photorefractive and photoexpansion effects in a van der Waals semiconductor - Anton A. Minnekhanov; Georgy A. Ermolaev; Alexey P. Tsapenko; Ilia M. Fradkin; Gleb I. Tselikov; Adilet N. Toksumakov; Aleksandr S. Slavich; Arslan B. Mazitov; Sergey A. Smirnov; Nikita D. Orekhov; Ivan A. Kruglov; Sergei A. Ivanov; et al. (Proceedings of the National Academy of Sciences, 2026)
Nanophotonics relies on precise nanoscale structuring, yet conventional fabrication techniques remain complex and costly. Layered van der Waals (vdW) materials, with their intrinsic anisotropy and high refractive indices, offer a promising route toward simplified nanostructuring and tunable optical functionality. However, no vdW material has previously been shown to exhibit a strong photorefractive effect—a key requirement for light-based modulation. Here, we report a giant photorefractive response (Δ n up to 0.3) in crystalline arsenic trisulfide (As 2 S 3 ), observed at low optical intensities. In addition to refractive-index modulation, light exposure enables controlled thickness tuning of As 2 S 3 . The material exhibits a giant photoexpansion of up to 7%, depending on the illumination intensity, which may originate from light-induced generation of point defects, consistent with molecular-dynamics modeling. Building on this photoexpansion effect, we introduce a maskless nanopatterning technique based on continuous-wave laser writing, achieving ~500 nm pitch (~50,000 dpi) without the need for ultrafast lasers. The combination of high photosensitivity, anisotropy, ease of exfoliation and transfer, and optical transparency positions vdW As 2 S 3 as a practical platform for integrated photonics, adaptive optics, reconfigurable photonic elements, and dense optical encoding.